Subwavelength metrology of Al wire grating employing finite difference time domain method and Mueller matrix polarimeter - Adhikari, Achyut (2018)
Wire grid polarizers (WGP), are sub-wavelength gratings with applications in display projection system due to their compact size, wide field of view and long-term stability. Measurement and testing of these structures are important to optimize their use. This is done by first measuring the Mueller Matrix of the WGP using a Mueller Matrix Polarimeter. Next the Finite Difference Time Domain (FDTD) method is used to simulate a similar Mueller matrix thus providing the period and step height of the WGP. This approach may lead to more generic determination of sub-wavelength structures including diffractive optical structures.